Hyperfine structure constants for neutral and singly ionized vanadium by Fourier transform spectroscopy data. (April 2022) - Ma, Huiting; Liu, Meina; Xu, Yixin; Pan, Lingyun; Dai, Zhenwen
Highlights: Fourier transform (FT) spectra were used to extend the study of the hyperfine structure (HFS) of V I and V II energy levels. HFS constants A for 53 levels of V I from 28, 313 to 52, 948 cm −1 were determined, of which 46 results are reported for the first time, as far as we know. Our study increased the total number of HFS constants A to 416 V I levels. HFS constants A for 56 levels of V II from 36 to 72, 952 cm −1 were determined, of which 50 results are reported for the first time, as far as we know. Our study increased the total number of HFS constants a to 126 V II levels. Abstract: The hyperfine structure (HFS) for V I and V II were investigated using the archival data recorded by the Fourier transform spectrometer (FTS) at the US National Solar Observatory (NSO) with a fitting program written by us. The magnetic dipole HFS constant A values for 53 levels of V I between 0 and 52, 948 cm −1 and for 56 levels of V II between 36 and 72, 952 cm −1 are obtained, of which 46 results for V I and 50 results for V II are reported for the first time, as far as we know. And to our knowledge, so far, the A constants of 370 levels of V I and 76 levels of V II have been measured in literature. The new results obtained in this work supplement more experimental HFS data very useful in astrophysics and atomic physics etc..